The prognostic relevance of pleural effusion in patients with COVID-19: a German multicenter study : cardiothoracic imaging - Bucher, Andreas M.; Dietz, Julia; Ehrengut, Constantin; Müller, Lukas; Schramm, Dominik; Akinina, Alena; Drechsel, Michelle; Klöckner, Roman Trutz; Sieren, Malte Maria; Isfort, Peter; Sähn, Marwin-Jonathan; Fink, Matthias A.; et al. (Clinical imaging, 2025)
Purpose - This study evaluates the prognostic significance of pleural effusion (PE) in COVID-19 patients across thirteen centers in Germany, aiming to clarify its role in predicting clinical outcomes. - Methods - In this retrospective analysis within the RACOON project (Radiological Cooperative Network of the COVID-19 pandemic), 1183 patients (29.3 % women, 70.7 % men) underwent chest CT to assess PE. We investigated PE's association with 30-day mortality, ICU admission, and the need for mechanical ventilation. - Results - PE was detected in 31.5 % of patients, showing a significant correlation with 30-day mortality (47.5 % in non-survivors vs. 27.3 % in survivors, p < 0.001), with a hazard ratio of 2.22 (95 % CI 1.65-2.99, p < 0.001). No significant association was found between PE volume or density and mortality. ICU admissions were noted in 46.8 % of patients, while mechanical ventilation was required for 26.7 %. - Conclusion - Pleural effusion is present in a significant portion of COVID-19 patients and independently predicts increased 30-day mortality, underscoring its value as a prognostic marker. Its identification, irrespective of volume or density, should be a priority in radiological reports to guide clinical decision-making.
Online verfügbar: 26. September 2024, Artikelversion: 11. November 2024
Gesehen am 27.05.2025